Expression of senescence-related CD161 promotes extranodal NK/T cell lymphoma by affecting T cell phenotype and cell cycle - Chengxun Jin; Xin Li; Chaohe Zhang (BMC, 2024)
Abstract Purpose The intention of this work is to probe the role of senescence-related gene CD161 in extranodal NK/T cell lymphoma (ENKTL). Methods This study used H2O2 to establish three distinct in vitro oxidative stress aging models (NKL, SNT-8, and YT). Western blotting was employed to assess the levels of two iconic aging proteins, MMP1 and P53, and flow cytometry was utilized to investigate cell cycle and the expressions of CD4, CD8, and CD161. Cell viability was evaluated via the CCK-8 assay. The transcriptome analysis assessed the differential gene expression between the control and aging group of NKL. In vivo, we established a BALB/c mice aging tumor model. After 15 days, the mice were euthanized to harvest tumors. ELISA was employed to measure aging indicators in the mouse tissues. Flow cytometry was utilized to assess the levels of CD4, CD8, and CD161 in tumor samples. Hematoxylin-eosin (HE) staining was performed to evaluate the structure and cellular morphology of the tumor tissue. Results In the NKL, SNT-8 and YT aging models, the levels of MMP1 and P53 proteins were significantly increased. Flow cytometry results indicated that all three cell types exhibited marked arrest in the G1 phase. Compared with the control group, the expressions of CD4 and CD161 in the aging group were significantly increased, while the expression of CD8 was decreased. Transcriptome analysis revealed 2,843 differentially expressed genes (DEGs) between the control and aging groups, with 2,060 up-regulated and 783 down-regulated genes identified. Following CD161 knockdown, cell viability of three cell types in the aging group was significantly reduced compared to the control group. The G1 phase of the cells was significantly interrupted. The expressions of CD4 and CD161 were significantly increased, and the expression of CD8 was decreased. However, in the aging + si-CD161 group, a partial alleviation of oxidative stress was observed with a reduction in CD161 expression levels. Animal experiments demonstrated that knockout of CD161 can inhibit tumor progression and partially mitigate oxidative stress. Conclusions CD161 may inhibit ENKTL tumor development by regulating cell cycle and T-cell phenotype.